Validation of the English version of the arrhythmia-specific questionnaire in tachycardia and arrhythmia (ASTA): a Rasch evaluation study - Ulla Walfridsson; Håkan Walfridsson; Melissa E. Middeldorp; Prashanthan Sanders; Kristofer Årestedt (SpringerOpen, 2022)
Abstract Background Patient-reported outcome measures are important in person-centered care, providing valuable information about patients' experiences. Disease-specific questionnaires add important information about a certain disease in comparison to generic questionnaires. Questionnaires need to be validated in the targeted population to achieve reliable data. The purpose with the study was to use Rasch measurement theory to evaluate the English version of the ASTA questionnaire. Methods The Rasch model theory was used to evaluate global and item fit, targeting, response category functioning, local independency, unidimensionality, differential item functioning (DIF) for gender and age, and reliability. Results The study included 202 patients undergoing DC conversion or catheter ablation at the Centre for Heart Rhythm Disorders at the University of Adelaide, Australia. The mean age was 67 years and 30% were women. Most patients had atrial fibrillation (n = 179), others had atrial flutter or had a combination. One of nine items demonstrated unsatisfactory model fit in the ASTA Symptom scale and two of 13 in the ASTA Health-Related Quality of Life (HRQoL) scale. Unidimensionality was supported for both scales. The targeting was acceptable except for the lower end of the scales. Both scales showed reversed thresholds for the response categories "quite a lot" and "a lot" (eight of ASTA symptoms and 12 of ASTA HRQoL items). Some problems with local dependency were detected in both scales. The reliability (person separation index) was satisfactory: 0.75 for the ASTA symptom scale and 0.77 for the ASTA HRQoL scale. No DIF for gender and age were detected. Conclusions The English version of the ASTA questionnaire demonstrated satisfactory measurement properties according to the Rasch model. However, it needs to be evaluated in patients with other arrhythmias. The response categories should be considered as well as DIF in further validation. The ASTA questionnaire can be used for assessments of symptoms and HRQoL between groups of different ages and genders in patients with arrhythmia.